Kajian Sifat Fisik Tanah pada Lahan Kering Beriklim Kering di Kecamatan Wulla Waijelu Kabupaten Sumba Timur - Yonce Melyanus Killa,; Melycorianda Hubi Ndapamuri,; Edmilson Umbu Ratu,; Matias Umbu Teul, (Journal Galung Tropika, 2024)
Dry land with a dry climate (LKIK) is suboptimal land that has the potential to be developed. A higher evapotranspiration rate than rainfall characterizes this land, so this land is in a condition of water shortage. One of the areas with LKIK conditions is Wulla Waijelu District, East Sumba Regency, East Nusa Tenggara Province, which is one of the areas with LKIK conditions. This area has not utilized its land potential because the land's condition, especially the soil's physical properties, has yet to be discovered. Therefore, this research was conducted to determine the physical properties of the land so that its use was based on the capabilities of the land. This research was conducted in Wulla Waijelu District in June-August 2023. This research used survey methods and sampling at predetermined points for four land uses. The observation variables are soil texture, permeability, porosity, bulk weight, and field capacity water content. The research results show that the research results provide varying values between land use and observation variables. Soil texture consists of clay, sandy clay, dusty clay, sandy loam, and dusty clay. Permeability criteria are medium, medium to fast, and fast, with soil porosity ranging from 22.8-70.3%. Soil bulk weight is between 0.96-1.6 gr/cm3, with field capacity water content varying from 22.8% to 70.3%.